The use the of digital image correlation in a strain analysis - Frankovský, Peter; Virgala, Ivan; Hudák, P.; Kostka, Ján (Zielona Góra: Uniwersytet Zielonogórski)
This paper provides a description of the basic principles and procedures that can be found in strain measurements by means of an experimental method known as the digital image correlation (DIC) while using the correlation system Q-400 and the evaluation software Istra4D. The second part of the paper includes the application of DIC method in strain measurements on a sample made of a PS-1A photoelastic material while using the correlation system Q-400.
Keywords: digital image correlation (DIC); correlation system Q-400; software Istra4D; strains